Dr. Helen Alice Bean; Dr. Norman Miller Brown; Dr. Frederick George (Ted) Elliott; Dr. Hjalmar Wilfred Johnson; Dr. Joseph E. Tremblay - Association, Canadian Urological (Canadian Urological Association Journal, 2013)